Cardioprotectant Effect Of Bay Leaf Extract (Syzygiumpolyanthum) On Myocardium Thickness Of Rat Heart - Rizky Trimaulidia; Dian Yuliartha Lestari (Universitas Muhammadiyah Malang, 2021)
High salt diet and prednisone administration will increase blood pressure which chronically causes heart muscle remodeling so that it appears macroscopically as left ventricular hypertrophy. Bay leaf extract contains flavonoids which can lower blood pressure and decrease left ventricular thickening. To determine the effect of bay leaf extract (Syzygiumpolyanthum) on the left ventricle thickening of rat heart (Rattus norvegicus wistar strain) in hypertensive model. True experimental post-test only controls group design with simple random sampling technique. The subjects of this study were 25 male Wistar rats aged 2-3 months weighing 150-200 grams. Rats were induced with prednisone 1.5 mg/ KgBW / day in 2% NaCl for 6 weeks followed by administration of bay leaf extract at a dose of 70 mg/ KgBW, a dose of 140 mg/ KgBW, and a dose of 280 mg/ KgBW. Data analyzed by One Way ANOVA, Post Hoc Bonferroni, followed by Linear: One Way ANOVA test showed significant differences between treatments (p = 0.000). The Bonferroni Post Hoc test concluded that there were significant differences in the treatment of the P2 and P3 groups. Linear regression test obtained R square 0.663 and obtained the equation Y = 1965.838 - 1.275X. The extract of bay leaf (Syzygiumpolyanthum) has an effect on decreasing the left ventricle thickening of the white male rat heart (Rattus norvegicus wistar strain) hypertension model.